Effector and Central Memory Poly-Functional CD4+ and CD8+ T Cells are Boosted upon ZOSTAVAX® Vaccination - Sei, Janet J.; Cox, Kara S.; Dubey, Sheri A.; Antonello, Joseph M.; Krah, David L.; Casimiro, Danilo R.; Vora, Kalpit A. (Frontiers in Immunology, 2015)
ZOSTAVAX® is a live attenuated varicella-zoster virus (VZV) vaccine that is licensed for the protection of individuals ≥ 50 years against shingles, and its most common complication, post-herpetic neuralgia. While IFN responses increase upon vaccination, the quality of the T cell response has not been elucidated. By using polychromatic flow cytometry, we characterized the breadth, magnitude, and quality of ex vivo CD4+ and CD8+ T cell responses induced 3 – 4 weeks after ZOSTAVAX vaccination of healthy adults. We show, for the first time that the highest frequencies of VZV-specific CD4+ T cells were poly-functional CD154+IFNγ+IL-2+TNFα+ cells, which were boosted upon vaccination. The CD4+ T cells were broadly reactive to several VZV proteins, with IE63 ranking the highest amongst them in the fold-rise of poly-functional cells, followed by IE62, gB, ORF9, and gE. We identified a novel poly-functional ORF9-specific CD8+ T cell population in 62% of the subjects, and these were boosted upon vaccination. Poly-functional CD4+ and CD8+ T cells produced significantly higher levels of IFNγ, IL-2, and TNFα compared to mono-functional cells. After vaccination, a boost in the expression of IFN by poly-functional IE63-and ORF9-specific CD4+ T cells, and IFNγ, IL-2, and TNFα by ORF9-specific poly-functional CD8+ T cells was observed. Responding poly-functional T cells exhibited both effector (CCR7−CD45RA−CD45RO+), and central (CCR7+CD45RA−CD45RO+) memory phenotypes, which expressed comparable levels of cytokines. Altogether, our studies demonstrate that a boost in memory poly-functional CD4+ T cells, and ORF9-specific CD8+ T cells may contribute towards ZOSTAVAX efficacy.